The Influence of School Administration for Educational Institutions at VHS 15 Merangin - Yahya, Yahya; Nifriza, Ifna; Wulandari, Diana (International Journal of Educational Dynamics, 2023)
Schools are integrated educational institutions, where there are supporting components within an institution, this is school administration and this cannot be separated from competent personnel who can handle this matter, so to handle administration in a school institution, competent personnel are needed according to their expertise. This research aims to determine the influence of school administration services on Vocational High School (VHS) 15 Merangin students, to determine the influence of teacher administration services on VHS 15 Merangin students, and the influence of administration on the VHS 15 Merangin institution itself. In this research, researchers used quantitative research methods, with instrument testing taking place at VHS 15 Merangin. The sample used was 34 students. Data collection through questionnaires, documentation, and observation. The results of the research showed that there was a good influence of school administration services on students, namely 25 students (73.5%), and the remaining 9 students (26.5%) were influenced by other factors. There is a positive influence of teacher administrative services on students, namely 27 students (79.4%), and the remaining 7 students (20.6%) are influenced by other factors.